A Analysis of Employee Career Planning at Pt ABC - Dwiyantoro, Iqbal; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to comprehensively understand employee career planning at PT ABC. The specific objectives are: 1) To analyze the stages of career planning implementation, 2) To identify the methods used to establish career planning aspects, and 3) To describe the corrective actions taken by PT ABC to address challenges in employee career planning. This research employs a qualitative approach with a narrative analysis method. The sampling technique used is purposive sampling, selecting informants with in-depth knowledge based on specific criteria. Data is collected through observation, interviews, and documentation (primary data), as well as literature reviews from books, previous studies, and relevant scientific articles (secondary data). The data analysis involves stages of collection, reduction, presentation, verification, and conclusion drawing. The findings reveal that PT ABC implements career planning through annual evaluations and development programs. However, obstacles such as employees’ lack of engagement, primarily caused by schedule conflicts with work deadlines, hinder its effectiveness. To address these issues, PT ABC raises awareness about the importance of career development and adjusts schedules to encourage participation. Overall, while PT ABC’s career planning program has shown progress, improvements are still needed, particularly in time management, to ensure greater employee involvement and effectiveness in achieving career development goals.